Networks of Hagiographic Imagination and the Camino - Rose Walker (Ad Limina, 2025)
The five books of the Codex Calixtinus present many instances of natural objects and artefacts encountered by pilgrims and travelers in the environment along the camino to Santiago. The Codex offers insight into their genesis, functions, and agency, showing how their material qualities engaged with the sensorial sphere and the imagination of beholders. This article is concerned with the issues these objects raise in relation to memory, materiality, and the senses. Scattered along the road to Santiago, these objects formed a material landscape of the Camino, creating a route of sensorial memory.